Gender in Education Settings: Case Study of English Primary School Textbooks in Armenia - Kojoyan, Ani; Aghakhanyan, Inna (Armenian Folia Anglistika, 2020)
School textbooks do not only transmit information and knowledge, but also educate and teach students certain social roles, norms, standards, behaviors, attitudes and manners. From this perspective, it becomes important to analyze those textbooks and observe what norms are standardized, what behaviors are encouraged and what stereotypes are circulated and normalized through them. The present article focuses on the analysis of gender in terms of gender roles and stereotypes in English textbooks of primary schools in Armenia.